2010
DOI: 10.1017/s0033291710001881
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive transcranial magnetic stimulation reduces cortisol concentrations in bulimic disorders

Abstract: These results suggest that rTMS applied to the left DLPFC alters HPAA activity in people with a bulimic disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 52 publications
3
24
1
2
Order By: Relevance
“…There was also a non-significant tendency to show greater cortisol reduction in the final exposure session, compared to the first session, in the pure exposure group. These results are consistent with the expected positive effect on this neuroendocrine response of weight normalization and bulimic symptoms reduction in women with BN after successful treatment (Claudino et al, 2011;Field et al, 1998;Neudeck et al, 2001;Strong, 2010). One possible explanation is that as treatment progressed and the discomfort levels decreased throughout the sessions (and the positive thoughts and feelings increased), the patients perceived greater control and were more tolerant of negative emotions.…”
Section: Discussionsupporting
confidence: 79%
“…There was also a non-significant tendency to show greater cortisol reduction in the final exposure session, compared to the first session, in the pure exposure group. These results are consistent with the expected positive effect on this neuroendocrine response of weight normalization and bulimic symptoms reduction in women with BN after successful treatment (Claudino et al, 2011;Field et al, 1998;Neudeck et al, 2001;Strong, 2010). One possible explanation is that as treatment progressed and the discomfort levels decreased throughout the sessions (and the positive thoughts and feelings increased), the patients perceived greater control and were more tolerant of negative emotions.…”
Section: Discussionsupporting
confidence: 79%
“…Interestingly, previous, single-session, sham-controlled, fast rTMS studies in healthy women showed no modulatory effects on the HPA axis after left or right DLPFC (Baeken et al, 2009b), although right DLPFC rTMS effects were observed, in another sample of healthy women, when controlling for baseline, state anxiety (Baeken et al, 2011). Other studies showed that fast rTMS over the left DLPFC decreased salivary cortisol levels in patients with depression (Baeken et al, 2009a) and bulimia (Claudino et al, 2010). The potent, polarity-dependent tDCS effects on the HPA axis observed in our study might be explained by the simultaneous bifrontal modulation, since previous models have suggested that HPA activity decreases or increases according to left and right DLPFC activity, respectively (Cerqueira et al, 2008).…”
Section: Discussionmentioning
confidence: 87%
“…However, Baeken et al (2011) found, in another sample, that rTMS decreased cortisol levels when controlling for baseline state anxiety. Other studies reported that rTMS decreased salivary cortisol levels in patients with depression (Baeken et al, 2009a) and bulimia (Claudino et al, 2010). Zwanzger et al (2003, 2007) evaluated rTMS effects on the “area under the curve” of cortisol response in two studies: in depressed patients, the authors explored whether therapeutical rTMS would change the cortisol response to the dexamethasone cortisol suppression test that is characteristically impaired in depression, finding no rTMS effects.…”
Section: Resultsmentioning
confidence: 90%
“…Of note, NIBS effects on these systems occurred mostly in the context of stress response – e.g., negative image visualization (Brunoni et al, 2012b) and 16 h fasting (Binkofski et al, 2011) or in clinical samples, such as depression (Baeken et al, 2009a), bulimia (Claudino et al, 2010), and anxiety (Baeken et al, 2011). Likewise, such effects occurred primarily during neuromodulation of DLPFC, an area implicated in the pathophysiology of stress and affective disorders (Koenigs and Grafman, 2009).…”
Section: Discussionmentioning
confidence: 99%